(untitled) (Journal of Telenursing (JOTING), 2023)
This study aims to determine interventions that can be carried out to reduce the risk of falls and the incidence of falls in patients. The research method used is scoping review through databases, namely CINAHL, MEDLINE, Scopus, and Proquest. The results showed that out of 14 articles, 13 articles showed a reduced risk of falling or falling events. Interventions provided to prevent the risk of falling use technology, video media, posters, and e-learning modules. Forms of giving information include providing education, training, and webinars. Fall risk interventions are provided to patients, caregivers, multidisciplinary teams, families, and communities. The material provided varies, such as the nursing care process, medication fall safety, fall risk prevention strategies, forms of physical exercise, and technology systems. In conclusion, the method for preventing patients at risk of falling and falling must get support. Support can be done through training, education, and organizational support. Keywords: Falls, Nursing, Organization, Fall Prevention, Fall Risk